Peningkatkan Hasil Belajar Matematika Tentang Luas Bangun Datar Melalui Metode Pembelajaran Kooperatif Tipe STAD Bagi Siswa Kelas III SDN 001 Rambah Hilir Tahun Pelajaran 2016/2017 - Kasmawati Kasmawati (Indonesian Journal of Basic Education, 2018)
Abstract, The purpose of this study is to improve the results of learning mathematics Class III Semester 2 on the subject matter of calculating the area of flat wake in SDN 001 Year 2016/2017. The result of the research shows the use of STAD type cooperative method can improve student learning outcomes in the mathematics class III SDN 001. This is seen from the Cycle I of the use of STAD type cooperative method was increased from 17 students as many as 11 students (64.70%) who achieved Minimum Exhaustiveness Criteria (KKM). And there is a significant increase in cycle II that is as many as 13 students (76.47%) who reach the Minimum Exhaustiveness Criteria (KKM)